2008
DOI: 10.21273/horttech.18.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Optimum In-row Distances for Potato Minituber Production

Abstract: Two field trials were conducted in the Dominican Republic to determine the influence of in-row distances on ‘Granola’ potato (Solanum tuberosum) minituber yield and economic returns. Seedlings generated from in vitro microtubers were transplanted in open-field raised beds at in-row distances of 0.20, 0.25, 0.30, 0.35, and 0.40 m to compare their minituber yield. In-row distances affected potato minituber weight and number per hectare and per plant. Increasing in-row distances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
2
8
0
4
Order By: Relevance
“…The high minituber size at low planting density may be due to the reduced competition among plants for nutrients and water and the observed increase in vegetative growth under low density plantation which in turn could increase photo-assimilate partitioning into tubers. These results agree with those of Santos and Rodriguez (2008) and; Dimante and Gaile, (2016) who obtained more minituber yields and numbers at high plantlet density. It was also reported by Van der Veeken and Lommen, (2009) that low density planting of in vitro plantlets increased tuber number and shoot branching, while high density reduced the time for minituber formation, which may positively affect total yield by the time of harvest.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high minituber size at low planting density may be due to the reduced competition among plants for nutrients and water and the observed increase in vegetative growth under low density plantation which in turn could increase photo-assimilate partitioning into tubers. These results agree with those of Santos and Rodriguez (2008) and; Dimante and Gaile, (2016) who obtained more minituber yields and numbers at high plantlet density. It was also reported by Van der Veeken and Lommen, (2009) that low density planting of in vitro plantlets increased tuber number and shoot branching, while high density reduced the time for minituber formation, which may positively affect total yield by the time of harvest.…”
Section: Discussionsupporting
confidence: 92%
“…In recent report, (Sharma et al, 2014) found that planting at density of 150 microtubers/m 2 gave more number of minitubers than at 66 microtubers/m 2 , and minituber size was higher at lower planting density. Santos and Rodriguez (2008) suggested that plant density variations could affect above and below ground biomass accumulation, and subsequently tuber number and yield.…”
Section: Discussionmentioning
confidence: 99%
“…The most suitable row line distances were recommended as 20 and 25 cm intervals. In our study, Mt weight per plant and number of Mts per hectare were obtained higher comparing to Santos and Rodriguez (2008). For the values of Mt number per plant were similar to Santos and Rodriguez (2008).…”
Section: Resultssupporting
confidence: 68%
“…In many cases all these applications and factors may interact; therefore, when one of them is changed, other yield parameters can be changed (Dimante and Gaile, 2014;Sharma and Pandey, 2013). Santos and Rodriguez (2008) were evaluated the yield of Mts by planting the germinated microtubers in 20, 25, 30, 35 and 40 cm rows in open field. Mt weight per plant was 195 g and 269 plant -1 at 20 cm and 40 cm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Bitki başına mini yumru sayısı ise 20 ve 25 cm sıra üzeri mesafelerde 6.5 adet ortalama ile en yüksek bulunmuş ve en uygun sıra üzeri mesafeler bu aralıklar olarak tavsiye edilmiştir. Araştırmada sera koşullarında Santos and Rodriguez (2008)'e göre dekardan daha yüksek mini yumru sayısı ve bitki başına mini yumru sayısı elde edilmiştir.…”
Section: Materyal Ve Yöntemunclassified